Links: de plek waar de Jong werd neergeschoten (Rosespoorstraat); rechts: Oranjeboomstraat. Uit: Wereldkroniek, 18-4-1903
Links: de plek waar de Jong werd neergeschoten (Rosespoorstraat); rechts: Oranjeboomstraat. Uit: Wereldkroniek, 18-4-1903.